Praktik Revenue Sharing dan Implikasinya pada Kesejahteraan Masyarakat - Thoha, Akhmad; Sudarma, Made; Triyuwono, Iwan; Ludigdo, Unti (Jurnal Akuntansi Multiparadigma, 2011)
Revenue Sharing Practices and Its Implication to Society Welfare. This research aims to develop the concept of Revenue Sharing and Its Implications on Welfare Society based on empirical data collected during the study in the SRB Asri Jember. This research used Grounded Theory approach with systematic procedures through the analysis of coding and categorization that comes with giving a name in each category, further divided into an array of conception. Revenue Sharing Practices are derived from based to Al-Quran and Al-Hadis laden with moral values ââand spiritual Islam that upholds honesty, transparency, and welfare of the community so as to ensure the creation of justice reduced economic inequality. Implications of Revenue Sharing Concept formulated consists of two principles, namely: revenue sharing as a form of profit sharing and loss based on mutual agreement between the bank and the customer and falah the welfare of society through the distribution of income through Alqordhul hasan funds sourced from the zakat, infaq and shodaqoh. Pratik Revenue Sharing dan Implikasinya pada Kesejahteraan Masyarakat. Penelitian ini bertujuan untuk menyusun konsep Revenue Sharing dan Implikasinya pada Kesejahteraan Masyarakat berdasarkan data empirik di BPRS Asri Jember. Penelitian ini menggunakan pendekatan Grounded Theory dengan prosedur sistematis melalui analisis coding dan kategorisasi. Praktik Revenue Sharing bersumber dari Alquran dan Hadis sarat dengan nilai-nilai moral dan spiritual Islami yang menjunjung tinggi kejujuran, transparansi, dan kesejahteraan masyarakat sehingga dapat menjamin terciptanya keadilan berkurangnya kesenjangan ekonomi. Konsep Implikasi Revenue Sharing yang dirumuskan terdiri dari dua prinsip, yaitu: revenue sharing sebagai bentuk bagi hasil/rugi berdasarkan kesepakatan bersama antara bank dengan nasabah dan falah yaitu mewujudkan kesejahteraan masyarakat melalui distribusi pendapatan melalui dana Alqordhul hasan yang bersumber dari zakat, infaq dan shodaqoh. melalui pembentukan.